The Effect of Hypoxia and Metformin on Fatty Acid Uptake, Storage, and Oxidation in L6 Differentiated Myotubes - Musutova, Martina; Elkalaf, Moustafa; Klubickova, Natalie; Koc, Michal; Povysil, Stanislav; Rambousek, Jan; Volckaert, Beatriz; Duska, Frantisek; Trinh, Minh Duc; Kalous, Martin; Trnka, Jan; Balusikova, Kamila; et al. (Frontiers in Endocrinology, 2018)
Metabolic impairments associated with obstructive sleep apnea syndrome (OSA) are linked to tissue hypoxia, however, the explanatory molecular and endocrine mechanisms remain unknown. Using gas-permeable cultureware, we studied the chronic effects of mild and severe hypoxia on free fatty acid (FFA) uptake, storage, and oxidation in L6 myotubes under 20%, 4%, or 1% O2. Additionally, the impact of metformin and the peroxisome proliferator-activated receptor (PPAR) β/δ agonist, called GW501516, were investigated. Exposure to mild and severe hypoxia reduced FFA uptake by 37% and 32%, respectively, while metformin treatment increased FFA uptake by 39% under mild hypoxia. GW501516 reduced FFA uptake under all conditions. Protein expressions of CD36 (cluster of differentiation 36) and SCL27A4 (solute carrier family 27 fatty acid transporter, member 4) were reduced by 17% and 23% under severe hypoxia. Gene expression of UCP2 (uncoupling protein 2) was reduced by severe hypoxia by 81%. Metformin increased CD36 protein levels by 28% under control conditions and SCL27A4 levels by 56% under mild hypoxia. Intracellular lipids were reduced by mild hypoxia by 18%, while in controls only, metformin administration further reduced intracellular lipids (20% O2) by 36%. Finally, palmitate oxidation was reduced by severe hypoxia, while metformin treatment reduced non-mitochondrial O2 consumption, palmitate oxidation, and proton leak at all O2 levels. Hypoxia directly reduced FFA uptake and intracellular lipids uptake in myotubes, at least partially, due to the reduction in CD36 transporters. Metformin, but not GW501516, can increase FFA uptake and SCL27A4 expression under mild hypoxia. Described effects might contribute to elevated plasma FFA levels and metabolic derangements in OSA.